Environmental Influences on Cactus Pear Fruit Yield, Quality and Cold Hardiness and Development of Hybrids with Improved Cold Hardiness (Journal of the Professional Association for Cactus Development, 1997)
Development of freeze-hardy clones of cactus pears is the principal limitation to establishing commercial cactus-pear plantations in Texas, Arizona, and New Mexico (Uphof, 1916; Griffiths, 1915; Nobel,1990; Russell and Felker 1987; Gregory et al., 1993). While most winters in south Texas are sufficiently mild that little or no damage to cactus pears occurs, about every 10 to 15 years, severe cold fronts originating in Canada reach the southern portions of the United States. These severe weather patterns offer little opportunity for plants to become hardened off because these fronts may bring the first below freezing temperatures of the winter, as well as below- freezing temperature for 24 to 48 consecutive hours, with minimum temperatures of S12°C (Gregory et al., 1993).